2014
DOI: 10.1001/jamaophthalmol.2014.1698
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Spectral-Domain Optical Coherence Tomography Retinal Thickness Measurements and Conversion to Equivalent Time-Domain Metrics in Diabetic Macular Edema

Abstract: Diabetic Retinopathy Clinical Research Network Writing Committee IMPORTANCE Understanding measurement variability and relationships between measurements obtained on different optical coherence tomography (OCT) machines is critical for clinical trials and clinical settings.OBJECTIVE To evaluate the reproducibility of retinal thickness measurements from OCT images obtained by time-domain (TD) (Stratus; Carl Zeiss Meditec) and spectral-domain (SD) (Cirrus; Carl Zeiss Meditec, and Spectralis; Heidelberg Engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 14 publications
1
61
0
Order By: Relevance
“…14 The DRCR Network also showed that sd-OCT measurement can be reliably converted to standard Stratus time-domain OCT measurement with conversion equations. 13 If CMT of 250 µm in time-domain OCT is converted to the sd-OCT, it will range from 290.2 µm to 313.4 µm. We chose 300 µm as the cut-off value for the upper limit of normal macular thickness to distinguish abnormal from normal because our Carl Zeiss Cirrus OCT is a sd-OCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The DRCR Network also showed that sd-OCT measurement can be reliably converted to standard Stratus time-domain OCT measurement with conversion equations. 13 If CMT of 250 µm in time-domain OCT is converted to the sd-OCT, it will range from 290.2 µm to 313.4 µm. We chose 300 µm as the cut-off value for the upper limit of normal macular thickness to distinguish abnormal from normal because our Carl Zeiss Cirrus OCT is a sd-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…6 In recent years, there has been a move towards the use of newer treatment modalities, such as intravitreal injection of anti-vascular endothelial growth factor (VEGF) agents that are superior to the traditional laser treatment in the management of CSME. [7][8][9][10][11][12][13][14] Screening for DR has been proven to be cost-effective in reducing significant vision loss by early detection of the pathology. [15][16][17] This will subsequently reduce the financial burden caused by vision complications of DR on the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Following repair of the Cirrus, both Cirrus and Spectralis OCT scans were captured at 150 subsequent participant visits, enabling development and validation of a linear conversion function for CSMT from Spectralis to Cirrus, similar to work done previously by the DRCR.net. 22 Prediction error of the conversion function was evaluated using a bootstrap cross-validation routine and was estimated to be 8.4 μm (95% CI [8.4, 8.6]). Spectralis values were converted and utilized as Cirrus CSMT values for the 12% of key visits at which the Cirrus scan was not performed.…”
Section: Methodsmentioning
confidence: 99%
“…The DRCR Network has published 2 manuscripts in the last year that provide some metrics for the conversion of SD-OCT data from the Cirrus (Carl Zeiss Meditec), the Spectralis (Heidelberg Engineering), and the RTVue (Optovue) to TD-OCT (Carl Zeiss Stratus) standards. [11,12] The analysis provided by the network is useful in evaluating and comparing results across trials and developing machine-specific thresholds on SD-OCT for interventions in subsequent clinical trials.…”
Section: Other Recent Contributions To Diabetic Retinopathy Researchmentioning
confidence: 99%